MEMBANGUN PENDIDIKAN KARAKTER DALAM MASYARAKAT - Sri Suyanta (Universitas Islam Negeri Ar-Raniry, 2013)
Character education is a necessity across the area, time and age. Character education is absolutely necessary not only in school, but also at home and in other social environments. It was prioritized since the past, present and future. Even today the students in character education is no longer for an early childhood but also adult and even the elderly age. Therefore character education should be designed and implemented systematically and simultaneously to help the students understand the human behavioral values which are associated with someoneself, fellow human beings, the environment and his or her Lord. Character education can be reached through three stages, namely socialization of the introduction, internalization, application in life.